Analysis of the Relationship of Income and Knowledge to Habits of Open Defecation in Langkat Regency in 2022 - Nadhira Marsha Audiva Harahap; Nurmaini Nurmaini; Taufik Ashar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze of the relationship of income and knowledge to habits of open defecation in Langkat Regency in 2022. The type of research used in this study is a quantitative study with a cross sectional approach. The population of this study is all heads of families in Langkat Regency, totaling 256,025 Families. The sample in this study is the subject taken from the population of the community residing in 2 Sub-Districts from 23 Sub-Districts in Langkat Regency. The total of each sample is Tanjung Pura and Stabat Districts 4 and 2. Data analysis used bivariate analysis. The results show that there is a significant relationship between income and knowledge to habits of open defecation in Langkat Regency in 2022.